The Spirit and Elements of Malaysian Multiculturalism in Chuah Thean Teng’s Batik Paintings - Wenyan, Geng; Wan Mohamad Daud, Wan Samiati Andriana; Tahir, Azian (Idealogy Journal, 2023)
This paper examines the batik paintings of Chinese artist Chuah Thean Teng in the context of Malaysia’s multicultural society. Batik, an ancient traditional craft in Malaysia, was initially produced on textiles through wax and dyes and is often applied to daily clothing and objects. As such, the motifs and elements of batik paintings are closely related to the local culture and have a high symbolic value. Chuah Thean Teng has improved and developed the batik process into a work of art with aesthetic value. This paper aims to understand the social and cultural climate of the time through a generalised analysis of the results of Chuah Thean Teng to evaluate the artistic elements embedded in the batik works. The paper adopts an art historical research approach, which consists mainly of form and context analysis. The study is descriptive, with data in the form of text and images, including the artworks themselves, publications, books, journals, and other official records. Chuah Thean Teng, a Chinese artist, has inherited and evolved the traditional Malaysian batik art by seeking artistic inspiration in a culturally diverse environment. His work is a hybrid expression, reflecting the exchange and borrowing between cultures. This is in keeping with the historical context of the time and also conveys modern Malaysian art’s inclusiveness, diversity, and richness. As an essential part of contemporary Malaysian art, batik painting is itself a sign of modernity. It is hoped that this study will help to enrich the research and analysis of Malaysian batik painting and, through it, generate interest in batik painting and provide knowledge and methods of interpreting the content of the artwork.   KEYWORDS: Multiculturalism, Chuah Thean Teng, Batik paintings, Malaysian Chinese Artists, Iconography.